Modulation of Glycine Receptor-Mediated Pain Signaling in vitro and in vivo by Glucose - Hussein, Rama Ashraf; Ahmed, Marwa; Breitinger, Hans-Georg; Breitinger, Ulrike (Frontiers in Molecular Neuroscience, 2019)
The inhibitory glycine receptor plays an important role in rapid synaptic inhibition in mammalian spinal cord, brainstem, higher brain centres, and is involved in transmission of nociceptive signals. Glucose and related mono- and disaccharides potentiate currents mediated by recombinant α1, α1-, and α3 glycine receptors. Here, we confirmed the specific potentiation of α3 glycine receptor signalling by glucose through (i) patch-clamp electrophysiology on recombinant receptors and (ii) by verifying in vitro data in a mouse model in vivo. Mice were intraperitoneally injected (IP) with glucose (2 g/kg) or vehicle, and then challenged with sublethal doses of strychnine (0.2 mg/kg and 0.5 mg/kg). Pain-related behaviour was assessed using two established models, (i) touch sensitivity tests using von Frey filaments, and (ii) hotplate assay. We observed a reduction of pain sensitivity in glucose-treated mice relative to vehicle-treated control mice. Injection of strychnine resulted in an increased sensitivity to tactile and heat stimuli, which was reversed in the presence of glucose. Analgesic effects of glucose were more pronounced in von Frey experiments, consistent with the established use of this model for neuropathic pain. Overall, glucose showed mild analgesic effects, and was able to compensate strychnine-induced allodynia in mice. Since action of strychnine is specific for glycine receptor, these experiments show for the first time an in vivo potentiation of glycine receptor activity by glucose and suggest a molecular mechanism for glucose-mediated analgesia.